Empowering Pregnant Women to Increase Knowledge of High Risk in Pregnancy - Ita Noviasari; Ika Agustina; Levi Tina Sari; Maria Ulfa; Wahyu Wibisono; Maratus Sholichah Fitriah Hajar Kusnianto; Ulfa Husnul Fata (STIKes Patria Husada Blitar, 2023)
High risk in pregnancy is a condition that can cause pregnant women and babies to become abnormal before birth. The danger signs of pregnancy must be understood and can be detected in the mother's pregnancy so that they can be handled properly because the danger signs in pregnancy can cause complications in pregnancy. This community service was carried out in Karanggayam Village, Srengat District, Blitar Regency. The implementation of the community service was on August 30,2022. The activities included: (1). Giving a pre-test in the form of a questionnaire to pregnant women, (2). Antenatal care activities (ANC), (3). Outreach activities about high-risk pregnancy, (4). Post-test in the form of a questionnaire. The counselling media used LCD media, laptops, videos and leaflets. The instrument used a questionnaire about high-risk pregnancy. Based on the results of the evaluation, it was found that 30% of pregnant women have poor knowledge, and only 20% had good knowledge. After being given an intervention in the form of counseling about high-risk in pregnant women, it was found that 70% had knowledge in the good category, and 30% in the sufficient category. It is expected to provide counseling to pregnant women about high-risk of pregnancies by using lecturing media, videos and leaflets.